Improved detection of rare, endangered and invasive trout in using a new large‐volume sampling method for eDNA capture. Issue 3 (24th June 2019) - Sepulveda, Adam J.; Schabacker, Jenna; Smith, Seth; Al‐Chokhachy, Robert; Luikart, Gordon; Amish, Stephen J.
Abstract: Environmental DNA (eDNA) detection probability increases with volume of water sampled. Common approaches for collecting eDNA samples often require many samples since these approaches usually use fine filters, which restrict the volume of water that can be sampled. An alternative to collecting many, small volume water samples using fine filters may be to collect fewer, large volume water samples using coarse filters that do not clog as rapidly. We used mesocosm experiments and field evaluations to compare coarse filter‐large water volume samples (hereafter large volume filter samples) versus fine filter‐small water volume samples (hereafter small volume filter samples) for detection and quantification of rainbow trout ( Oncorhynchus mykiss ) and bull trout ( Salvelinus confluentus ) DNA. We found that large volume filter sampling can be an effective approach for detecting DNA of low‐density target taxa. In mesocosm experiments, large‐volume and small‐volume water samples detected similar quantities of rainbow trout DNA. In the field, large volume samples more frequently detected bull trout DNA, had higher bull trout DNA copy number, and higher total DNA concentrations than small volume samples. However, sampling higher water volumes increased the potential for PCR inhibition so the DNA workflow had to be altered for large volume samples. Combining larger water volume samples with other strategies, like increasing PCR sensitivity and the number of PCR replicates, will improve detection of rare species, which is crucial for advancing conservation and ecological understanding. Abstract : We found that large volume (> 1000 L) water samples using coarse filters, as pictured, can be an effective approach for detecting DNA of low density salmonid fish in rivers.